The Role of Scholars of Bali Tribe in Establishing Educational Centers in Andalusia - Jassim, Ayat Abdul Jabbar Naseef; Thalij, Widad Kurdi (Journal of Ecohumanism, 2024)
By reviewing the history of Andalusia, many Arab tribes appear that were present in Andalusia and had an impact on scientific life, but the light was not shed on them. In this research, we tried to shed light on the role of scholars of the Bali tribe in establishing educational centers in Andalusia. We addressed the lineage of the tribe and then the role of the Kuttabs in education and the most famous scholars of the Bali tribe who contributed to the Kuttabs in Andalusia. We also addressed the role of mosques in the issue of education and the most famous scholars of the Bali tribe who studied in the mosque, as well as discipline and the places where scholars sit in order to teach and raise children.